Lack of Association between PTPN22 Gene+1858 C > T Polymorphism and Susceptibility to Generalized Vitiligo in a Turkish Population - Akbas, Halit; Dertlioglu, Selma Bakar; Dilmec, Fuat; Atay, Ahmet Engin (Korean Dermatological Assoc, 2014)
Background: Vitiligo is an autoimmune polygenic disorder characterized by loss of pigmentation due to melanocyte destruction. The PTPN22 gene +1858 C > T single nucleotide polymorphism (rs2476601) has been shown to be associated with various autoimmune disorders. Objective: The aim of this study was to investigate whether the PTPN22 gene +1858 C > T single nucleotide polymorphism is associated with susceptibility to generalized vitiligo in a Turkish population. Methods: One hundred and seven patients with generalized vitiligo, and one hundred and twelve gender-, age-, and ethnic-matched controls were enrolled in the study. Genotyping was done by polymerase chain reaction-restriction fragment length polymorphism. Results: The PTPN22 +1858 C > T genotype and allele frequencies of the generalized vitiligo patients did not differ significantly from those of healthy controls. Conclusion: We found no association between the PTPN22 +1858 C > T gene polymorphism and vitiligo susceptibility in Turkish generalizedvitiligo patients.
Keywords: Polymerase chain reaction-restriction fragment length polymorphism; PTPN22 gene; Vitiligo